Thematic analyses of participant survey responses following dermatology ECHO programs with dermoscopy: Practical tips and lessons learned - Black, T. Austin; Parbs, Joshua R.; Teixeira, Anthony J.; Cyr, Peggy; Nelson, Kelly C.; Stoddard, Henry; Seiverling, Elizabeth V. (Frontiers in Digital Health, 2023)
Introduction Skin cancer is a major public health concern in the United States, reflecting approximately one in every three cancer diagnoses. Despite the high incidence of skin cancer, access to dermatologists is limited, especially in rural areas. Primary care physicians play a pivotal role in the evaluation of skin conditions, but dermatology training gaps exist in primary care training programs. Objectives This study examines the use of the Project ECHO (Extension for Community Healthcare Outcomes) knowledge-sharing framework to provide dermoscopy and skin cancer detection training to primary care providers (PCPs). Methods Responses to surveys administered to participants in two separate dermoscopy-focused Project ECHO courses were analyzed. Survey responses were collected over a 4-year period for the two courses, which were delivered in Maine and Texas. Thematic analysis of the qualitative data was performed, revealing codes and subcodes that indicated several overall trends. Results Overall, most respondents indicated the ECHO sessions to be helpful, reporting an increase in confidence and knowledge in dermoscopy. Other codes reflected a positive reception of the learning materials and teaching styles. Furthermore, participant survey analyses highlighted areas of improvement for future ECHO course sessions. Conclusions This thematic analysis of Project ECHO courses in dermatology with dermoscopy demonstrates the feasibility of using virtual educational platforms to effectively teach PCPs about dermoscopy and skin cancer, with high levels of participant satisfaction. The need to keeping the educational sessions brief, avoid scheduling sessions on high-volume patient care days, and provide a means for participants to obtain hands-on training in the operation of a dermatoscope were among the top lessons learned.